SIMULATION OF SCREENING PERFORMANCE AND FLOW BEHAVIOR OF NON-COHESIVE AND COHESIVE MATERIAL ON BANANA SCREEN WITH DIFFERENT APERTURE SHAPES - Sin, IlChol; Kim, CholSong; Ryom, CholUng; Hong, WonChol (Asosiasi Peneliti Sriwijaya, 2025)
In this paper, the screening performance and particle flow of non-cohesive and cohesive materials in banana screens with different shapes of aperture are investigated. In our study, the particles have different cohesiveness, i.e. surface energy, depending on the case. Apertures are also rectangular in shape, with different aspect ratios and orientations according the cases. Based on the model, the screening process was simulated by DEM(discrete element method). The screening performance was evaluated in terms of the passing percent of undersize particles, and the flow characteristics were investigated based on the average velocity and the mass distribution of the particles on each panel. The results of the study can help in the design of aperture, structure and material of banana screen for screening of non-cohesive and cohesive materials.